A Randomized Controlled Trial Evaluating the Efficacy of a Psychoeducation Program for Families of Children and Adolescents With ADHD in the United Kingdom: Results After a 6-Month Follow-Up. Issue 5 (March 2020) - Ferrin, Maite; Perez-Ayala, Viviana; El-Abd, Samaa; Lax-Pericall, Teresa; Jacobs, Brian; Bilbow, Andrea; Taylor, Eric
Objective: Psychoeducation forms part of the current practice for ADHD; however, its efficacy is yet to be established.Method: Sixty-nine children/adolescents with ADHD were randomly assigned for their families to receive either a well-structured psychoeducation program ( n = 35), or belong to a control group (treatment-as-usual, n = 34).Results: One-way analyses of variance showed a statistically significant Treatment × Time interaction, for ADHD total symptoms, inattention/cognition, and hyperactivity/impulsivity subdomains according to the parents, the first two with medium-large effect sizes. The effects of the intervention on the ADHD total and the inattention/cognition domain persisted after 6 months follow-up. No significant differences in teacher ratings were found; however, an improvement in clinical functioning as measured by clinicians was observed.Conclusion: This psychoeducation program has shown effectiveness in reducing ADHD symptoms when compared with treatment as usual. Psychoeducation needs to be considered as a valid and additional approach in ADHD.